From Frugality to Investment: The Role of Financial Self-Efficacy in Shaping Investment Decision - Budiyono, Elizabeth Fiesta Clara Shinta; Sinugroho, Kezia Callista Odelyn (Review of Management and Entrepreneurship, 2026)
This study examines the role of financial self-efficacy in moderating the effect of frugal living on investment decisions among students. Understanding how financial self-efficacy influences investment choices is crucial, as students often face financial constraints and are influenced by both psychological factors and financial habits. A quantitative approach with a survey design was used to analyze the moderating effect of financial self-efficacy on frugal living and investment decisions among 117 students in Yogyakarta. Data were collected through a structured questionnaire and analyzed using SPSS version 25, including validity, reliability tests, descriptive statistics, normality tests, and multiple regression analysis. The study found that frugal living has a positive and significant effect on investment decisions among students. However, financial self-efficacy was not found to moderate the relationship between frugal living and investment decisions, indicating that frugal habits play a more dominant role in shaping investment choices. Limitations include the small sample size of 117 students from Yogyakarta and the exclusion of other factors influencing investment decisions. Additionally, the cross-sectional design limits the ability to assess behavioral changes over time. The findings suggest that promoting frugal living can improve investment decisions, highlighting the importance of financial discipline. The lack of moderation by financial self-efficacy implies that fostering practical financial habits is more important than boosting financial confidence. This study uniquely combines financial self-efficacy and frugal living, offering new insights into their role in student investment decisions.